Differences in postural disturbances between female adolescents handball players and nontraining peers - Jandric, Slavica Dj (Vojnosanitetski pregled, 2017)
Background/Aim. Physical activity and sport can influence the extent of the presence of the postural disturbances in children. The aim of this study was to investigate the occurrence of differences in the postural disturbances in female adolescents in relation to team handball training. Methods. This investigation involved 150 female adolescents with the average age of 13.2 ± 1.34 years divided into two groups (50 adolescents trained handball and 100 did non train it). Results. The study determined a statistically significant difference in the total number of postural disturbances between the two groups of adolescents (p
Keywords: adolescent; athletes; female; spinal curvatures; scoliosis; kyphosis; foot deformities